Un fonds documentaire en maréchalerie - Patrick Doffémont (In Situ)
Documenting the blacksmith’s trade. The constitution of a documentary collection devoted to the blacksmith’s and farrier’s trade allows for the history of this trade, which comprises an important technical and cultural heritage built up over the centuries, to be transmitted to younger generations. The documentation also helps understand the absence of this transmission between the 1950s and 1970s and to appreciate the situation today. Above all, however, it is necessary for the future, for training of young people in the farrier’s trade, and for understanding his identity and role in society.